EFFECT USING MIXED OF EXTRACT HERBS ON FEED CONSUMPTION, BODY WEIGHT GAIN AND FEED CONVERSION OF BROILER - Pea Mole, Yoseph E (Universitas Kanjuruhan Malang, 2015)
The aim ofÂ this research was to know effect using mixed of extract herbs on feed consumption, body weight gain, and feed conversion of broiler. 80 DOC strain MB-202 was arrange on complete randome design, 4 treatment, 4 replicated, The treatment were: 0%,10%,15%, and 20% herbs mixed wich given on drinking water. Herbs mixed include: ginger, garlic, turmeric, betel, ginger (Curcuma xanthorrhiza). Mixed herbs fermented with EM4 for two weeks. Basal feed was complete feed wich given ad libitum.Â Result of this research shown that there was significant effect using mixed of extract herbs on feed consumption (P<0.05), while there was no significant effect on body weight gain and feed conversion. Feed consumption (g/bird) of P1, P0, P3 and P2 were 3.572,70 g, 3.493,95 g, 3.445,35 g and 3.138,40 g respectively. Average body weight gain (g/bird) of P1, P0, P3 and P2 were 1.866,5 g, 1.855,475 g, 1.763,75 g, and 1.663,25 g respectively. It could be concluded that using 10 % mixed of extract herbal give the best performance of broiler.Keywords: Herbs, broiler, organic farmingÂ